Pojok Baca Sebagai Sarana Meningkatkan Semangat Literasi Siswa SD Negeri Perigi Raya - Iain, Saadah; Supriatin, Atin; Wati, Siti Nurrika; Murselina, Murselina; Saputra , Anggi (Lembaga Dongan Dosen, 2023)
Discusses the importance of reading corners in schools as a tool to increase students' interest and literacy skills. This research evaluates the positive impact of the reading corner by analyzing student participation, their level of interest in reading, and their literacy skills before and after the implementation of the reading corner. This research is based on the Asset Based Community Development (ABCD) approach using a qualitative method. The research results show that the reading corner is effective in increasing students' literacy enthusiasm. These findings support the importance of introducing a literacy-supportive environment in the school environment to develop students' reading and writing skills. This research provides valuable insight into how to improve literacy education at SD Negeri Perigi Raya.